Performance and Economics of Goat Production in Confinement on Feeding Soya Deoiled Cake and Groundnut Cake-Based Concentrate Mixture - Patil, P. V.; Dhage, M. O.; Salunke, V. M.; Ghoke, S. S. (International Journal of Bio-resource and Stress Management, 2022)
The present study was conducted for 12 weeks at Livestock farm complex, College of Veterinary and Animal Sciences, Udgir in Latur district of Maharashtra state in January–March, 2020 on 12 Osmanabadi goat kids of either sex divided into two groups of 6 kids in each group to study the growth performance, dry matter intake and economics of goat production on feeding soya deoiled cake and groundnut cake-based concentrate mixture. During the experiment, the kids were maintained intensively with same managemental practices. The group I and II were offered concentrate mixture containing soya deoiled cake and groundnut cake, respectively as a protein source. Each kid in the group was supplemented with 200 g of the prepared concentrate mixture day-1. All the kids were offered DHN6 green fodder (70%) ±Hedge Lucerne (30%) a-dlibitum and 100 g, 150 g and 200 g of Jowar straw daily kid-1 in first four weeks, mid four weeks and last four weeks of the experimental period, respectively. Daily feed intake, weekly body weights were recorded for 12 weeks. It was found that dry matter intake, weekly body weight gain and daily body weight gain was significantly more in kids of group I whereas, no particular trend in dry matter intake (percent BW) was found in between the groups. Net profit kid-1 was more in group I (2,129.67) than the group II (₹ 1339.98). It was inferred that the feeding of concentrate mixture with Soya doc as a protein source gives better performance and proved to be economical.